HRCT findings in COVID-19 suspected patients - Nasir, Joshua; Zulfiqar, Taiba; Ali, Abid (Medical Science Journal for Advance Research, 2023)
Background: Aims and Objective are to identify findings of suspected covid-19 patients. Method: This prospective cross-sectional study was carried at the radiology department of Sialkot Medical Complex, a private hospital in Sialkot. It included a total of 40 patients during one month and then SPSS was used for statistical analysis to find out the frequency of effected patients. Results: Out of 38 patients who were presented with suspicion of COVID in them, 36 patients were found to be having symptoms of COVID in CT scans. 2 patients were normal which are not included in the results. Conclusion: CT scan (computed tomography) is an excellent modality to identify COVID in a patient. It uses radiation to create image on the screen. It consists of a gantry and a control panel (computer). It has high diagnostic efficiency to identify covid-19.